Math for olympiad: a didactic proposal for high school from the perspective of the international mathematical olympiad - Paulo Vitor da Silva Santiago; Francisco Régis Vieira Alves (Journal of Advanced Sciences and Mathematics Education, 2022)
The concept of the International Mathematics Olympiad (IMO) in learning mathematics in the classroom is something that can inspire students by structuring didactic proposals. This study aims to present a didactic proposal from the perspective of the International Mathematics Olympiad , using digital technology, particularly the GeoGebra software to be included in the mathematics Olympiad discipline. For theoretical studies, the analysis of the mathematical elements of the structured images in the GeoGebra software and the identification of their properties is included, through the structuring of the Olympic teaching situation, which allows the subject to seek solutions to the posed mathematical problems. olympics and validating the teaching of geometry. This study describes the arrangements made to build Olympic math objects that will be applied by math teachers. The research methodology is based on bibliographic reviews from authors such as Alves, Santiago, Almouloud and Brousseau. It is proven that the GeoGebra software helps in the elaboration of mathematical examples and problem solving situations.